2016
DOI: 10.4274/jcrpe.2693
|View full text |Cite
|
Sign up to set email alerts
|

Adding Multiple Adipokines into the Model do not Improve Weight Gain Prediction by Leptin Levels in Newborns

Abstract: Objective:Most adipose tissue programming is realized in early life. Also, the postnatal three months, rather than the later phases of infancy, may be more relevant in the development of an adverse cardiometabolic risk profile. The adipokines phenotype, as a predictor of early-life weight gain, has been recently explored in cord blood. To determine whether in addition to leptin levels in cord samples, adiponectin, interleukin-6 (IL-6), monocyte chemoattractant protein-1 (MCP-1), resistin, plasminogen activator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…One study found cross‐sectional associations with metabolic risk markers including insulin resistance among children but with some indication that the different isoforms of resistin may create discrepant findings . Our findings regarding weight gain are similar to those of another study measuring cord blood resistin and other factors (including leptin and adiponectin) among 86 newborns, finding no association for weight gain at 3 months postpartum apart from leptin levels . However, we found that higher newborn resistin levels were associated with higher odds of being overweight at 2–3 years of age.…”
Section: Discussionsupporting
confidence: 82%
“…One study found cross‐sectional associations with metabolic risk markers including insulin resistance among children but with some indication that the different isoforms of resistin may create discrepant findings . Our findings regarding weight gain are similar to those of another study measuring cord blood resistin and other factors (including leptin and adiponectin) among 86 newborns, finding no association for weight gain at 3 months postpartum apart from leptin levels . However, we found that higher newborn resistin levels were associated with higher odds of being overweight at 2–3 years of age.…”
Section: Discussionsupporting
confidence: 82%
“…Leptin is an important afferent, peripheral, humoral signal to the appetite-regulating network in the hypothalamus and affects food intake and energy expenditure. It is an important predictor of weight gain even during early infancy ( 21 ). Therefore, low levels of leptin or its biological inactivity resulting from mutations in LEP may disturb metabolic balance, leading to severe obesity and related metabolic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…One study found mRNA expression of gene-encoded resistin was increased in adipose tissue from GDM when compared to a non-GDM group, and the expression level was related to insulin resistance [24]. Conflicting findings have been found regarding cord serum resistin and birthweight [25,26].…”
Section: Introductionmentioning
confidence: 99%